Examining the Validity of Traffic Stop Data: A Mixed-Methods Analysis of Police Officer Compliance. (March 2021) - Chanin, Joshua; Welsh, Megan
Police departments rely on administrative rules to set organizational priorities and establish systems of accountability. To that end, several departments require officers to submit data describing every traffic stop they conduct as a way of tracking officer activity and identifying any race-based disparities. This paper draws on an analysis of San Diego Police Department traffic stop records, as well as officer survey and interview data, to examine the validity of the traffic stop data gathered and the compliance-related motivations of officers. Findings indicate a 19 percent error rate in stop data submitted between 2014 and 2015, amidst evidence of substantial underreporting. Qualitative data suggest that officers see the policy as redundant and an infringement on more pressing aspects of their job. They doubt the ability of external stakeholders to interpret the data objectively and report a loss of morale, largely attributed to the perception that their actions are inaccurately racialized.